Sobre a circulação de livros e a leitura na colônia brasileira - Raylane Andreza Dias Navarro Barreto; Ester Fraga Vilas-Bôas Carvalho do Nascimento; Tâmara Regina Reis Sales (Araucaria)
In the perspective of history tied to the printed Cultural History, this article focuses on analysis of documentary records and bibliographic printed about Catholics and Protestants in colonial Brazil with the aim of investigating its circulation and diffusion of ideas. Based on the method of historical research this article brings Brazilian historiography, books, bookstores and readers as well as booksellers the modus operandi that contributed to the transmission of religious knowledge in the country and with different communities of readers originating not only from religious congregation, of students and scholars, but lay people who cared and did circulate ideas in different media beyond the book.